Fabrication of hollow nanoporous gold nanoshells with high structural tunability based on the plasma etching of polymer colloid templates. Issue 23 (30th May 2018) - Lee, Da Hoon; Park, Jung Su; Hwang, Jong Ho; Kang, Dooho; Yim, Sang-Youp; Kim, Joon Heon
Abstract : Hollow nanoporous gold nanoshells are fabricated by the size reduction of colloid templates and the sintering of AuNPs induced by plasma etching. Abstract : Recently, nanoporous gold nanoparticles have attracted great interest due to their optical and catalytic properties. However, most reports on their fabrication are based on the dealloying method. Here, we report a new fabrication technique for hollow nanoporous gold nanoshells (NPGNSs) with high structural tunability by sintering chemically synthesized gold nanoparticles (AuNPs) on the surface of polymer colloid particles. Size reduction of the colloid template by plasma etching induces contact of the AuNPs on the colloid surface. Elimination of the capping layers of AuNPs by plasma etching facilitates sintering of the contacted AuNPs. Complete removal of the colloid template after AuNP sintering results in hollow NPGNSs. A combination of AuNPs and polymer colloid templates of different sizes can change the structure and optical properties of hollow NPGNSs. Furthermore, AuNPs of different shapes, such as gold nanorods with a high aspect ratio and spherical AuNPs, can be used to make hollow NPGNSs, which gives more flexibility in tuning their structures. Our proposed fabrication technique based on shrinkage of templates and sintering of nanoparticles can be a new platform to prepare hollow nanoporous metal structures having nanoscale overall sizes with high structural tunability.